Increasing Taxa Sampling Provides New Insights on the Phylogenetic Relationship Between Eriobotrya and Rhaphiolepis - Dong, Zhanghong; Qu, Shaohong; Landrein, Sven; Yu, Wen-Bin; Xin, Jing; Zhao, Wenzhi; Song, Yu; Tan, Yunhong; Xin, Peiyao (Frontiers in Genetics, 2022)
Eriobotrya (Rosaceae) is an economically important genus with around 30 species. It is widely distributed in tropical and warm temperate regions of Asia, with most of its species in China, Myanmar, and Vietnam. However, Eriobotrya is often confused with the smaller genus Rhaphiolepis, and the phylogenetic relationships between the two genera are controversial. Here we present phylogenetic analyses of 38 newly generated Eriobotrya and Rhaphiolepis nrDNA together with 16 sequences of nrDNA and 28 sequences of ITS obtained from GenBank, representing 28 species of Eriobotrya and 12 species of Rhaphiolepis, in order to reconstruct highly supported relationships for the two genera. Contrary to previous research based on limited sampling, our results highlight the monophyly of Eriobotrya as well as Rhaphiolepis. The topology recovered here is consistent with key morphological synapomorphies such as the persistent sepals in Eriobotrya. Our findings show that increased sampling of taxa can provide a more robust phylogeny through reducing phylogenetic error and increasing overall phylogenetic accuracy.